Mouth-to-mouth ventilation through cardiopulmonary resuscitation, is there any other way? - Maimaitiming, Aini; Wang, Xiaohai; Chen, Jie; Zhang, Bing (Journal of Cardiology and Cardiovascular Medicine, 2021)
Objective: to provide and explore possibility of new idea that perform mouth-to-mouth ventilation through cardiopulmonary resuscitation. Methods: stage one was establishing the ventilation technique using cola bottles, stage two was measuring the tidal volume when different sized cola bottles were used. Result: the smallest sized cola bottle (500 ml) could also make obvious thorax rise in manikin CPR model. The tidal volume was 174.5 ± 9.1 ml, 220 ± 7.6 ml and 447 ± 15.9 ml respectively for 500 ml, 600 ml and 1.25 L cola bottles when using single hand performance. There were statistical differences (0.001) in tidal volume of different sized cola bottle by using one hand performance and two hands. Conclusion: Larger sized cola bottles (600 ml, 1.25 L) could be used as substitute ventilation technique for mouth-to-mouth ventilation in special circumnutates.